A clinical study to compare the efficacy of crushing of middle turbinate with lateral partial turbinectomy for concha bullosa - Ninnekar, Savita Z.; Gadag, Raveendra P.; Doreyawar, Venkatesh; Jasmine, Kadeeja P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Concha bullosa (CB), a pneumatized middle turbinate is most common variations of sino-nasal anatomy. Identified in approximately ~35% (range 14-53%) of patients, a large CB cause nasal obstruction, recurrent sinus infections and headache, may develop into mucocele or mucopyocele or affect olfaction. Endoscopic lateral partial turbinectomy (LPT) is the standard procedure for the treatment of CB. However, the recurrence of contact points and postoperative synechiae with subsequent frontal recess obstruction are common complications of this technique. Crushing of a pneumatized turbinate preserves the mucosa, less time consuming and carry less risk of complications. The aim of the study was to compare the efficacy of crushing with LPT for the treatment of CB. Methods: This was a prospective cohort study conducted by convenient sampling in the Department of ENT, KIMS, Hubli, Karnataka, India. In 53 patients, 43 with unilateral and 10 with bilateral CB satisfying the inclusion and exclusion criteria were subjected to either crushing (group A) or LPT (group B). The success of both techniques were compared based on the relief of symptoms assessed by the visual analogue scale, nasal endoscopy and computed tomography (CT) scan after 6 months of surgery. Results: The overall success rate of the outcome was equal between the two groups, with no statistical (p>0.05) difference. Conclusions: Crushing the CB is as efficient as LPT for the treatment of pneumatized middle turbinate. However, surgically crushed CB can get re-pneumatization in some patients.